Analisis Spasial Sebaran Demam Berdarah Dengue di Kota Tasikmalaya Tahun 2011–2015 - Andri Ruliansyah; Yuneu Yuliasih; Wawan Ridwan; Asep Jajang Kusnandar (ASPIRATOR - Journal of Vector-borne Disease Studies, 2017)
Tasikmalaya is one of the DHF endemic area in West Java. In 2012 Tasikmalaya Government set the status of DHF Outbreak. DHF cases spread across sub district. The purpose of this research is to recognize the spread of DHF incident in Tasikmalaya, so it can be used by surveillance in reducing the number of dengue cases. Efforts to reduce the number of dengue fever cases are by increasing surveillance knowledge about analysis of surveillance data. This research used cross-sectional design and spatial analysis of dengue cases in Tasikmalaya (2011–2015) using autocorrelation method of Moran index and nearest neighbour analysis. The research was conducted in Tasikmalaya, West Java. Research is carried out for 3 months in 2016. The result showed that DHF distribution showed positive spatial autocorrelation in every year from 2011 to 2015. The pattern of spread of dengue cases is cluster (occurs in clumps). So the areas where cases clustered occured are areas that are susceptible to dengue disease.